2015
DOI: 10.1159/000436967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Montelukast Monotherapy on Oxidative Stress Parameters and DNA Damage in Children with Asthma

Abstract: Background: There is ample knowledge reported in the literature about the role of oxidative stress in asthma pathogenesis. It is also known that the interaction of reactive oxygen species with DNA may result in DNA strand breaks. The aim of this study was to investigate if montelukast monotherapy affects oxidative stress and DNA damage parameters in a population of pediatric asthma patients. Methods: Group I consisted of 31 newly diagnosed asthmatic patients not taking any medication, and group II consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…22 However, our recent study showed that montelukast monotherapy does not overcome the oxidative stress produced by asthma in children. 23 In the study by Nadeem et al, plasma total antioxidant capacity and total protein sulfhydryls were found to be decreased in acute exacerbations of asthma compared to stable asthmatic patients. However, this work does not include a control group of healthy participants.…”
Section: Discussionmentioning
confidence: 95%
“…22 However, our recent study showed that montelukast monotherapy does not overcome the oxidative stress produced by asthma in children. 23 In the study by Nadeem et al, plasma total antioxidant capacity and total protein sulfhydryls were found to be decreased in acute exacerbations of asthma compared to stable asthmatic patients. However, this work does not include a control group of healthy participants.…”
Section: Discussionmentioning
confidence: 95%
“…We did not find any difference in plasma TOS, TAS, OSI levels, and UAS7 score between boys and girls ( p > 0.05). We excluded patients with concomitant asthma, allergic rhinitis, and atopic dermatitis from the study, because there are some studies showing that all these diseases are associated with elevated oxidative stress [ 22 24 ]. However, the frequency of concomitant allergic diseases in our CSU group was not significantly higher when compared to prevalence rates of allergic diseases in our city.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clinical trial data to support the use of antioxidants to prevent asthma or allergy development (54). Other than corticosteroids, which possess antioxidant and anti-inflammatory properties, other anti-asthmatic drugs, e.g., montelukast, did show conflicting results regarding their capacity to improve total antioxidant status and decrease oxidative damage (55, 56). …”
Section: Antioxidant Strategies For Asthma Treatmentmentioning
confidence: 99%